Structure-property correlation of semifluorinated 6-membered co-SPIs for proton exchange membrane - Mistri, Ershad Ali; Banerjee, Susanta; Komber, Hartmut; Voit, Brigitte (European Polymer Journal, 2015)
This article reports the synthesis, characterization and proton exchange membrane (PEM) properties of four new structurally different naphthalenetetracarboxylic dianhydride (NTDA)-based semifluorinated sulfonated copolyimides (co-SPIs) containing heterocyclic groups as well as phenyl ring with various catenation angles. To understand the structure-property correlation, the co-SPIs were prepared with a fixed sulfonation degree (70%, IEC ∼ 2.1) by using the fixed molar feed ratio of sulfonated diamine to the different non-sulfonated diamines. The structures of the different co-SPIs, namely, p-DTN70, m-DTN70, DPyN70, and DThN70 were confirmed by FTIR and NMR spectroscopy. All the co-SPIs showed high thermal stability for 5% weight loss temperature (290-300°C) in synthetic air. Transparent, flexible and membranes were prepared from the co-SPIs that showed tensile strength in the range of 50-65 MPa and Young's modulus values in the range of 1.6-1.84 GPa in wet condition. It was noticed that the dimensional and oxidative stability were higher for para-connecting co-SPI membrane (p-DTN70) than for meta-connecting membranes (m-DTN70, DPyN70 and DThN70). Whereas, the proton conductivity was found highest for meta-connecting m-DTN70 membrane (σ = 79.2 mS/cm at 90°C) due to the higher water uptake and better phase separated morphology of the membrane as observed by transmission electron microscopy analysis.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Proton exchange properties; Semifluorinated sulfonated polyimides; Structure-property correlation